Maternal Mortality in the United States. Issue 4 (July 2020) - Killion, Molly M.
Abstract : New data on maternity mortality in the United States was published in January 2020, the first time since 2007, due to a change in how maternal deaths were reported, and to allow states to begin using the new system. Our maternity nursing expert, Molly Killion, presents an overview of the results.